Practical considerations in die casting design - New Jersey Zinc Company (ADBS, 1948)
Size: 6 1/4 x 9. Pages are clean and tight, appearing as if unused. Extensively illustrated with b/w photos. Inside front cover is a plate which reads "This book presented to _____ by The New Jersey Zinc Company". Some of the chapters are: Ribs, Fins, Beads and Bosses Add to Utility of Die Castings/ Fillets and Edges; Wheels, Gears and Cams; Fastening Expedients; Piercing and Forming Possibilities.